2018
DOI: 10.1155/2018/9371895
|View full text |Cite
|
Sign up to set email alerts
|

Less Expansion of Short-Pulse Laser Scars in Panretinal Photocoagulation for Diabetic Retinopathy

Abstract: Purpose To compare the expansion rates of laser photocoagulation scars between the conventional laser and short-pulse laser using fundus autofluorescence (FAF). Methods Retrospective chart review. Conventional laser was performed on 6 eyes of 6 patients, and short-pulse laser was performed on 11 eyes of 8 patients with diabetic retinopathy. FAF images were obtained by Optos® 200Tx (Optos, Dunfermline, Scotland, UK) at 1, 3, 6, and 12 months after treatment. The average area of 20 photocoagulation scars was mea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
12
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 28 publications
1
12
0
Order By: Relevance
“…Eventually, the lateral expansion of scars after argon laser treatment considerably exceeds the expansion of those applied with the PASCAL system. 27 Extended elimination of hypoxic tissue might contribute to better neovascularization regression. 28 However, laser energy not only spreads laterally but also vertically.…”
Section: Discussionmentioning
confidence: 99%
“…Eventually, the lateral expansion of scars after argon laser treatment considerably exceeds the expansion of those applied with the PASCAL system. 27 Extended elimination of hypoxic tissue might contribute to better neovascularization regression. 28 However, laser energy not only spreads laterally but also vertically.…”
Section: Discussionmentioning
confidence: 99%
“…Higaki et al reported that the expansion rates of the laser lesion in short-pulse laser were significantly lower than those after conventional laser. [8] Our results showed a restoration of the choriocapillaris at 2 weeks, and the recovery continued with time and was almost normal appearing at 1 year in some lasered spots with our laser settings using OCTA. On the contrary, the outer retina and RPE were also disrupted in the lasered spots 1 year after the laser photocoagulation.…”
Section: Discussionmentioning
confidence: 52%
“…For these reasons, RS was reduced after laser therapy using the conventional focal/grid laser. In contrast, the advantages of short-pulse laser include reduced RPE/outer retina damage and smaller lesion size due to the reduced spread of heat [ 16 , 18 , 34 , 35 ]. Decreased lesion size may also be attributed to the stable RS after laser treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Notably, the patterned scanning laser has become popular as a less invasive laser therapy [ 11 ]. In addition, because tissue invasion depends on the time of laser exposure, the short-pulse laser method causes less thermal diffusion [ 16 , 17 ] as well as lowers the risk of damage to the outer retina and the lesion size [ 18 20 ]. Therefore, MAPC using short-pulse duration has several advantages for the treatment of the delicate macular area.…”
Section: Introductionmentioning
confidence: 99%